Demographic profile and high risk factors in morbidly adherent placenta - Rizvi, Syed Masuma; Fayaz, Farhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Morbidly adherent placenta with its variants is one of the most feared complications causing high morbidity and mortality in obstetrics. The main objectives of the study were to evaluate the demographic profile and risk factors in morbidly adherent placenta. Methods: A retrospective study was done in which case records of 40 patients diagnosed to have morbidly adherent placenta were reviewed. Demographic data including age, parity, gestational age and previous caesarean delivery or other uterine surgery, details of medical and obstetric history were recorded. Results: A total of 24232 deliveries were conducted in the hospital. 40 patients were confirmed to have morbidly adherent placenta. The average age of the patients was 31.8 years and the mean parity was 1.80. 95% percent of the patients were booked in the study centre and only 5% percent were unbooked. 80% of the patients were from the rural area and 20 % from the urban region. The average gestational age of the patient at diagnosis was 35.3 weeks and average gestational age at delivery was 36.2 weeks. The risk factors included previous caesarean section in 32 patients (80%) , with history of one C.S in 11 patients(27.5%),with two C.S in 19 patients(47.5%), and with history of three C.S in 4 patients (5%). 8 patients (20%) had history of both previous C.S and curettage and none had the history of curettage alone. Conclusion: Morbidly adherent placenta is a potentially life threatening condition. Management of such patients requires early recognition of high risk women based on their clinical risk factors, with accurate preoperative diagnosis, good maternal counselling and planning of delivery.